Za dejaven pouk književnosti - Žbogar, Alenka (Jezik in slovstvo, 2007)
The author describes an active method of teaching literature, referred to as problem-based creative teaching, foregrounding numerous advantages, cited bothin foreign and Slovene studies, as well as the disadvantages of this method. The article argues why the shift from the so-called teaching paradigm to the so-called learning paradigm is sensible also when teaching literature, and what consequences such a shift may have for the teaching of literature, inparticular for the teacher and the student.
Keywords: didactic method; didaktika; književnost; learning; literature; pouk; učenje